The Rhetoric of Death and Discipleship in Premodern Japan Sōchō's Death of Sōgi and Kikaku's Death of Master Bashō - Horton, H. Mack 1952-; Horton, H. Mack 1952- (Institute of East Asian Studies, University of California, 2019)
"Socho's Death of Sogi and Kikaku's Death of Master Basho provide information about iconic figures of premodern Japanese literature and their disciples, while themselves manifesting stylistic accomplishment. This book contains translations of both death accounts and introductions to the poets' lives, times, and works"
Includes bibliographical references and index.
Keywords: Matsuo, Bashō, -- 1644-1694.; Sōgi, -- 1421-1502.; Kikaku, -- 1661-1707 -- Criticism and interpretation.; Sōchō, -- 1448-1532 -- Criticism and interpretation.; Sōgi, -- 1421-1502; Sōchō, -- 1448-1532; Matsuo, Bashō, -- 1644-1694; Kikaku, -- 1661-1707; Japanese poetry -- Edo period, 1600-1868 -- History and criticism.; Japanese poetry -- 1185-1600 -- History and criticism.; Poésie japonaise -- 1600-1868 (Époque d'Edo) -- Histoire et critique.; Poésie japonaise -- 1185-1600 -- Histoire et critique.; LITERARY COLLECTIONS / Asian / Japanese; Japanese poetry -- Edo period; Japanese poetry; 1185-1868; Criticism, interpretation, etc.